Asplenium patagonicum (Aspleniaceae, Pteridophyta) nueva especie para Chile - Rodríguez Ríos, Roberto; Guzmán-Marín, Rosario (Gayana Botánica, 2017)
A new Chilean species, Asplenium patagonicum (Aspleniaceae, Pteridophyta), on the basis of the collections of vascular plants of South Chile is described. This Chilean fern has been reclassified from Asplenium monanthes L., given their differences in geographic distribution and morphological features. While A. patagonicum occurs in South Chile, A. monanthes presents a tropical distribution. The latter also is clearly distinguished from A. patagonium given its smaller size and different shape in their pinna; small, non-linear, and deltoid rhizome scales, and shorter general size.